2009
DOI: 10.1111/j.1468-3148.2008.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior Problems Inventory: Reliability and Factor Validity in Institutionalized Adults with Intellectual Disabilities

Abstract: Background The aim of this study was to reevaluate the reliability (internal consistency, inter-rater and re-test) and the factor structure of the Behavior Problems Inventory (BPI-01) with adults with intellectual disabilities who resided in a state-run developmental centre. Methods BPI-01 was administered to informants who had known participants for a minimum of 6 months. For study 1, data were collected in two samples: 100 residents who were selected based on the challenging behaviour targeted in their behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 34 publications
4
62
2
Order By: Relevance
“…Internal consistency of the Romanian BPI-01 was found to be good and even somewhat better than some studies on the English version have shown so far (González et al, 2009;Gray et al, 2009;Rojahn et al, 2001;van Ingen, Moore, Zaja, & Rojahn, 2010). For the NCBRF Social Competence subscales and for the six NCBRF Problem Behavior subscales internal consistency ranged between fair to excellent and generally fell in the ballpark found by other researchers working on the English version Gray et al, 2009;Lecavalier et al, 2006;Tassé & Lecavalier, 2000) and a French version (Girouard et al, 1998;Tassé & Lecavalier, 2000).…”
Section: Internal Consistencymentioning
confidence: 59%
See 1 more Smart Citation
“…Internal consistency of the Romanian BPI-01 was found to be good and even somewhat better than some studies on the English version have shown so far (González et al, 2009;Gray et al, 2009;Rojahn et al, 2001;van Ingen, Moore, Zaja, & Rojahn, 2010). For the NCBRF Social Competence subscales and for the six NCBRF Problem Behavior subscales internal consistency ranged between fair to excellent and generally fell in the ballpark found by other researchers working on the English version Gray et al, 2009;Lecavalier et al, 2006;Tassé & Lecavalier, 2000) and a French version (Girouard et al, 1998;Tassé & Lecavalier, 2000).…”
Section: Internal Consistencymentioning
confidence: 59%
“…In this study only the frequency scale data were collected because the frequency-scale and the severity-scale scores were shown repeatedly to be highly correlated (Rojahn, Aman, Matson, & Mayville, 2003;Rojahn et al, 2001). Various aspects of the validity and reliability of the BPI-01 have been explored in previous studies (e.g., González et al, 2009;Mansell et al, 2002;Mansell, Beadle-Brown, Macdonald, & Ashman, 2003;Matson & Rivet, 2008). The reliability of the BPI-01 (interrater agreement, test-retest, and internal consistency) has been shown to vary from good to excellent.…”
Section: Instrumentsmentioning
confidence: 96%
“…Behavior problems can cause physical injury to the aggressors themselves and to other individuals, impairing adaptation to social environments, including the family and school [1][2][3][4][5] -a scenario that underscores the importance of assessing this phenomenon and plan interventions when necessary. Some examples of typical aggressive responses are kicking, pushing, biting, scratching, and destroying things.…”
Section: Introductionmentioning
confidence: 99%
“…It was designed and has been widely used for persons with ID of all age ranges and functioning levels (González et al 2009;Rojahn et al 2001). It captures three dimensions of challenging behaviours: self-injurious behaviour (SIB), self-stimulating behaviour (SSB), and aggressive/destructive behaviour.…”
Section: Behaviour Problems Inventory (Bpi-01)mentioning
confidence: 99%
“…The global prevalence of ID is between 1% and 3% in the general population (Emerson & Einfeld 2011). In Hong Kong, the prevalence of intellectual disability (ID) is about 1-1.4% of the Challenging behaviour is common among individual with ID because challenging behaviour is often interpreted as a desire for attention or an expression of distress resulting from their limited communication and language understanding abilities (González et al 2009), especially for those severe and profound ID (Vlaskamp et al 2003;Vlaskamp & Nakken 1999).…”
Section: Introductionmentioning
confidence: 99%